(untitled) (Proceedings of the International Conference on Future of Education, 2021)
The acquisition of requisite reading skills plays a crucial role in scaffolding learning and more so when children start their education. These reading skills form an important pivot around which most learning revolves. Nevertheless, studies globally indicate that majority of school-age pupils are not being taught the relevant reading skills at an appropriate age and grade hence most of them attain the age of eleven years before acquiring these skills. The integral role played by the teacher in enabling learners to acquire reading skills cannot be over-emphasized. They are, in fact, an important axis around which all educational processes revolve including the success in the acquisition of the children‟s literacy skills. The purpose of this study was to find out the impact of teacher interpersonal characteristics on the acquisition of reading skills among grade three pupils in public primary schools in Bungoma County, Kenya. Vygotsky‟s (1978) theory was fundamental to this study. A descriptive survey research was adopted in the study focusing on grade three pupils, their class teacher and the headteachers in Bumula Sub-County. Simple random sampling and purposive sampling techniques were used to select the study sample of 32%. Data was collected using questionnaires, interview schedules and reading tests for grade three pupils to determine their level of reading skills. The researcher designed a pupil test to determine the levels of reading across the Grade III Learners. The study found out that teachers‟ interpersonal characteristics had an impact on the acquisition of reading skills among the grade III learners. The study further established that Grade III pupils in Bungoma County have overall poor reading skills as manifested by their dismal sound recognition, comprehension, word recognition, and reading fluency. Furthermore, the study established that Grade III teachers are neither aware nor apply their interpersonal skills, but rely on their skills to help Grade III learners acquire reading skills. The study recommended that Bungoma County‟s Ministry of Education should use these findings for policy implementation as a way or improving teacher interpersonal relationships, through modification of the curriculum of teacher training colleges